Implementing a Flipped Learning Approach With TPACK in Grades 6 to 9 - Delanoy, Nadia; El-Hacha, Jasmine; Miller, Monica; Brown, Barbara (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
In this design-based study, a flipped learning approach using audio-visual resources as prelearning activities was examined in grades 6, 7, and 9 with four teachers and 65 students over one school year. The purpose of this study was to explore the implementation of a technology-enhanced pedagogy in science, math, and social studies. The implementation was sequenced to provide students who were also learning the English language with an opportunity to practice engaging with curriculum concepts through viewing prelearning videos with language tailored by the teacher and with embedded questions, prior to in-classroom learning activities. The technological, pedagogical, and content knowledge (TPACK) framework was used to inform the instructional design for the flipped learning activities. Monthly teacher-researcher professional learning sessions were held, and data were gathered from teachers’ reflections and a student survey. Results indicated that teachers had more class time to support students with enrichment, remediation, small group work, and active learning. Students reported that the prelearning video activities benefited their learning and complemented in-class learning activities. This study serves to inform teachers and schools considering implementation of flipped learning to support students’ understanding of content knowledge and English language learning, and researchers studying designs using flipped learning sequences.